Mapping of a Semantic Field: Disputed Terms of Migration and How They Can Be Catalogued (KULT_online, 2025)
The inventory Disputed Terms of Migration provides an in-depth insight into society’s engagement with migration by capturing discursive and semantic shifts, transformations, and innovations in ‘migration terms.’ A reflexive approach uncovers conflict areas, discourses and power structures. This collection offers the reader more than a brief overview of different ‘migration terms,’ it also sheds light on the dynamics of language, power, and society.